Методичні засади реалізації релігієзнавчого компонента у закладах загальної середньої освіти Франції - Лаухіна, Інна (Studies in Comparative Education, 2015)
У статті йдеться про можливості запровадження у зміст національної шкільної освіти Франції знань про релігію, розглядається проблема поєднання світських принципів сучасної освіти та реалізації релігієзнавчого компонента (блоків знань про релігію) у навчальних програмах французької загальноосвітньої школи, виокремлено основні методичні підходи до впровадження релігієзнавчих знань, які є найбільш оптимальними при викладанні школярам знань про релігію, проаналізовано зміст релігієзнавчого компонента в державних шкільних програмах початкової та середньої школи (колежі та ліцеї) Франції. Визначено, що у французьких колежах та ліцеях надається перевага основним методичним прийомам, які є найбільш оптимальними при викладанні школярам знань про релігію. Аналіз навчальних програм засвідчив, що зміст блоків релігієзнавчих знань перебуває на експериментальній стадії: з’являються авторські програми, деякі з них можна назвати інноваційними. Згідно з позицією багатьох французьких дослідників, запровадження релігієзнавчого компонента в навчальні програми має обмежений характер, невирішеними залишаються питання щодо порівняльної методики вивчення релігій. В статье речь идёт о возможности введения в содержание национального школьного образования Франции знаний о религии, рассматривается проблема сочетания светских принципов современного образования и введения религиеведческого компонента (блоков знаний о религии) в учебные программы французских общеобразовательных школ, выделены основные методические подходы, которые являются наиболее оптимальными в преподавании школьникам знаний о религии, дан анализ содержания религиеведческого компонента в государственных школьных программах начальной и средней (коллежи и лицеи) школе Франции, акцентировано внимание на ограниченном характере знаний о религии во французских школах, а также на недостаточной теоретической базе исследования религиозных фактов и явлений. The article describes the ability of providing the knowledge about religion into the content of national school education in France. The problem of connecting the secular principles of modern education and the realization of religious components (areas of knowledge about religion) to the curriculum of French secondary school is raised. The main methodological approaches to the providing of religious knowledge are defined. They are the most optimal when conducting religion at school. The content of religious component in state school curriculum for primary and secondary schools in France is analyzed. The main circumstances of providing religious components in school curriculum are defined. The author emphasizes the limited character of knowledge about religion in French schools and a limited theoretical basis of investigating religious factors and features. The article describes the ability of providing certain areas of knowledge about religion implicitly being included into the content of national school education in France. So, educational material with correspondent content can be used during the French classes to help students in learning particular expressions, concerning religion. The usage of this item is much more effective at the history classes. The content of religions component is widely used being included to the curriculum of the majority of colleges and lyceums in France. Knowledge of definite content, combined in blocks, is included into the studying programme of different subjects, especially history of arts, history, geography, philosophy, language and literature of France. They are located concentrically with the progressive increase of complexity, considering interdisciplinary connections and the complementarity of subjects with the help of each. The authors of studying programs give their recommendations to use historical documents, maps, masterpieces (paintings, architecture, sculpture, literature, music) and biblical texts while teaching within the limits of certain topics and rubrics. At the present stage the implementation of the religious component is realized into the content of state secondary education in France in rather dynamical and innovational manner.